IMPLEMENTASI PROGRAM BAJAK GRATIS BRIGADE ALSINTAN BAGI PETANI SEBAGAI PROGRAM UNGGULAN PEMERINTAH DAERAH KABUPATEN TANAH DATAR - Fadel Muhammad; Rahmadani Yusran (LPPM Universitas Abdurrab, 2024)
This study aims to determine the Supporting Factors and Inhibiting Factors in the Implementation of the Free Plowing Program of the Alsintan Brigade for Farmers as a Leading Program of the Tanah Datar Regency Government. In this study, the researcher used a qualitative descriptive method where the method aims to describe what happened according to the conditions when the research was conducted. Data collection techniques in this study were interviews and documentation. Data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The results of the study showed that the Implementation of the Free Plowing Program of the Alsintan Brigade had supporting factors, including First, the existence of clear regulations, with the legal basis being Regent Regulation Number 54 of 2022. This regulation provides definite guidance and framework for all parties involved, including local governments, alsintan managers, and farmer groups. Second, support from agricultural extension workers, who are responsible for providing direction, guidance, and counseling to farmers, as well as assisting them in the use and maintenance of agricultural machinery (alsintan). The inhibiting factors include First, the limited service quota in the free plowing program. Second, the Free Plowing Program has not fully met the needs of farmers today. Farmers need more availability of fertilizer at affordable prices, because the expensive price of fertilizer is very burdensome for their production costs.